Thematic Based Private Vocational School Learning Chomparison Analysis In One Sheet Lesson Plan - sufiyanto, Mohammad Imam; Roviandri, Roviandri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The existence of new policies in the field of education is often interpreted as having changed the curriculum even though this is a common thing. The point is how learning practices in schools will become better, more efficient, and more effective. Likewise with the policy of drafting a one-sheet RPP which was initiated the Minister of Education and Culture to help reduce the burden on teachers in the field implementing learning. In simple terms, actually several RPP pages that previously could be summarized/abstracted into just one-sheet, then select the components that are considered core and must exist. There are also other components that can be attached or even removed, because it could be implied and expressed in the existing core components. However, for prospective teachers, it is better if they continue to study the lesson plans with the full component version and then learn to abstract into one-sheet RPP.